2007 International Conference on Field Programmable Logic and Applications 2007
DOI: 10.1109/fpl.2007.4380746
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Switched Run-Time Adaptive Network-on-Chip for Image Processing Applications

Abstract: Since the 1990s reusable functional blocks, well known as IP-Cores, have been integrated on one silicon die. These Systems-on-Chip (SoC) used a bus-based system for intermodule communication. Technology, performance and flexibility issues require the introduction of a novel communication system called Network-on-Chip (NoC). Around 1999 this method was introduced and since then has been investigated by several research groups with the aim to connect different IP-Cores through an effective, flexible and scalable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…To have more flexible bus connections it has been shown that data flow can be steered by using look-up-tables (LUTs) based routing [5]. Thus it is possible to implement a switch box which can change the dataflow by writing one configuration frame.…”
Section: Technology Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…To have more flexible bus connections it has been shown that data flow can be steered by using look-up-tables (LUTs) based routing [5]. Thus it is possible to implement a switch box which can change the dataflow by writing one configuration frame.…”
Section: Technology Preliminariesmentioning
confidence: 99%
“…To be able to set multilayer bus connections during runtime, the partial bitstreams do not include any connection to any of the layers. This connection is established during configuration by changing the corresponding bits of the bitstream on the fly as shown in principle in [5]. Reconfiguration of the bus structure can be realized through Read-Modify-Writeback method as presented in [14] (see II).…”
Section: Reconf Areamentioning
confidence: 99%
“…The first solution addressed in [5] is called circuit switched. This approach allows modules, which are willing to communicate, to establish a physical connection by setting some multiplexers on the communication links.…”
Section: A Current Existing Approachesmentioning
confidence: 99%
“…Actual research work in this area shows, that the switched based network integrated on Xilinx FPGAs, can be reconfigured in the time frame of 20µs. Certainly this time differs with the size of the selected FPGA as described in [12]. In [12] the registers controlling the switches of the network are aligned in a CLB row of the FPGA.…”
Section: Static Module (Persistentmentioning
confidence: 99%
“…Certainly this time differs with the size of the selected FPGA as described in [12]. In [12] the registers controlling the switches of the network are aligned in a CLB row of the FPGA. Therefore the described approach can be used by exploiting the dynamic and partial reconfiguration feature of the Xilinx FPGA.…”
Section: Static Module (Persistentmentioning
confidence: 99%